{4-Hydroxy-N'-[(2-oxido-1-naphthyl-O) methylidene] benzohydrazidato-2N', O} dimethyltin (IV) - Fasihuddin B, Ahmad; Md Abu, Affan; Norrihan B, Sam; Edward RT, Tiekink (International Union of Crystallography, 2010)
Two independent but very similar molecules comprise the asymmetric unit of the title compound, [Sn(CH3)2- (C18H12N2O3)]. Each Sn atom is coordinated by two methyl groups and two O atoms and an N atom from the dinegative tridentate ligand. The resultant C2NO2 donor set defines a coordination geometry intermediate between square-pyramidal and trigonal-pyramidal, with a small tendency towards the former. +Zigzag chains running along the a axis mediated by O—HN hydrogen bonding characterize the crystal packing. These are connected into layers in the ab plane by a combination of C—HN and – [centroid–centroid distances = 3.658 (2) and 3.6740 (18) A˚ ] interactions. The layers are connected along the c axis via C—HO interactions.